Dual fluorophore doped silica nanoparticles for cellular localization studies in multiple stained cells. (1st March 2015) - Shahabi, Shakiba; Treccani, Laura; Dringen, Ralf; Rezwan, Kurosch
Graphical abstract: Abstract: Fluorescently labeled nanoparticles (NPs) are used in a wide range of biomedical and nanotoxicological studies to elucidate their interactions with cellular components and their intracellular localization. As commonly used fluorescence microscopes are usually limited in their performance to a few channels which detect the emitted fluorescence light in the red, green and blue color range, the simultaneous colocalization of accumulated fluorescent NPs with cellular markers is often difficult and remains a challenge due to spectral overlay of NP fluorescence and fluorescence of stained cellular components. To overcome this problem we have synthesized three different photostable dual-labeled fluorescent core/shell silica NPs with high fluorescence intensity and well-defined shape, size and surface chemistry. The synthesis route of dual fluorophore doped silica (DFDS) NPs was based on a water-in-oil microemulsion method and includes the separate incorporation of two fluorophores in the core or shell. The suitability of DFDS for colocalization studies was assessed and successfully demonstrated with human osteoblast cells. Parallel visualization of DFDS NPs with two separate microscope channels allowed cellular NP uptake and discrimination from fluorescently stained cellular components, even in triple stained cells that show fluorescence for the cytoskeleton protein actin (green), the nucleus (blue) and collagen (red). Our results demonstrate the feasibility and straightforwardness of the approach for colocalization studies at a single-cell level to discern clearly the accumulation of NPs from triple-stained cellular components. Such NPs with multiple fluorescence characteristics have a great potential to replace single fluorescent NPs for in vitro studies, when multiple staining of cellular components is required.